Enhancing Security of Health Information Using Modular Encryption Standard in Mobile Cloud Computing - Shabbir, Maryam; Shabbir, Ayesha; Iwendi, Celestine; Javed, Abdul Rehman; Rizwan, Muhammad; Herencsár, Norbert; Lin, Jerry Chun-Wei (IEEE, 2021)
Despite the numerous and noticeable inherited gains of Mobile Cloud Computing (MCC) in healthcare, its growth is being hindered by privacy and security challenges. Such issues require the utmost urgent attention to realize its full scale and efficient usage. There is a need to secure Health Information worldwide, regionally, and locally. To fully avail of the health services, it is crucial to put in place the demanded security practices for the prevention of security breaches and vulnerabilities. Hence, this research is deliberated on to provide requirement-oriented health information security using the Modular Encryption Standard (MES) based on the layered modeling of the security measures. The performance analysis shows that the proposed work excels, compared to other commonly used algorithms against the health information security at the MCC environment in terms of better performance and auxiliary qualitative security ensuring measures.

Despite the numerous and noticeable inherited gains of Mobile Cloud Computing (MCC) in healthcare, its growth is being hindered by privacy and security challenges. Such issues require the utmost urgent attention to realize its full scale and efficient usage. There is a need to secure Health Information worldwide, regionally, and locally. To fully avail of the health services, it is crucial to put in place the demanded security practices for the prevention of security breaches and vulnerabilities. Hence, this research is deliberated on to provide requirement-oriented health information security using the Modular Encryption Standard (MES) based on the layered modeling of the security measures. The performance analysis shows that the proposed work excels, compared to other commonly used algorithms against the health information security at the MCC environment in terms of better performance and auxiliary qualitative security ensuring measures.
Enhancing Security of Health Information Using Modular Encryption Standard in Mobile Cloud Computing
Keywords: MES; Health Information Security; Mobile Cloud Computing; Requirement-oriented approach; Modular Protection-based Computing; MES; Health Information Security; Mobile Cloud Computing; Requirement-oriented approach; Modular Protection-based Computing